2019
DOI: 10.5694/mja2.50143
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic spinal cord injury in Victoria, 2007–2016

Abstract: Objective To investigate trends in the incidence and causes of traumatic spinal cord injury (TSCI) in Victoria over a 10‐year period. Design, setting, participants Retrospective cohort study: analysis of Victorian State Trauma Registry (VSTR) data for people who sustained TSCIs during 2007–2016. Main outcomes and measures Temporal trends in population‐based incidence rates of TSCI (injury to the spinal cord with an Abbreviated Injury Scale [AIS] score of 4 or more). Results There were 706 cases of TSCI, most t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 24 publications
(27 reference statements)
3
14
2
Order By: Relevance
“…Similar to the findings in the US [ 40 ] and Australia [ 2 ], falls were the most important external cause for SCI mortality in all age groups, especially in the elderly. Motor vehicle crashes were an important cause of SCI death in the 24-65-year age group, which might be explained by the 8.5­year increase in life expectancy during the past two decades and the greater proportion of elderly people living with chronic diseases at risk of fall related injuries and death [ 41 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Similar to the findings in the US [ 40 ] and Australia [ 2 ], falls were the most important external cause for SCI mortality in all age groups, especially in the elderly. Motor vehicle crashes were an important cause of SCI death in the 24-65-year age group, which might be explained by the 8.5­year increase in life expectancy during the past two decades and the greater proportion of elderly people living with chronic diseases at risk of fall related injuries and death [ 41 ].…”
Section: Discussionsupporting
confidence: 85%
“…Traumatic brain injury (TBI) and spinal cord injury (SCI) are injuries of the brain and spinal cord, leading to the functional alteration or pathological changes [ 1 , 2 ]. Both the TBI and SCI are significant global public health issues which contribute to the excessive health-care and economic burden because of the loss of productivity and increased health-care costs [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this present study, in-hospital and six-month mortality were 21.84% and 11.76%, respectively, compared to reported mortalities for patients with cervical cord injuries of 4.0-28%. 6,13 Advanced age, a higher level of injury, cause of SCI, late surgery against early surgery, and presence of respiratory failure on admission have been suggested as contributing factors 6,16 whereas in this study multivariate analysis showed the level of injury and respiratory failure as the only independent predictors of in-hospital mortality. 4,13 There are some explanations about the impact of a higher level of injury on mortality-patients with a higher level of cervical cord injury are generally accompanied by a higher rate of respiratory failure, more severe neurological dysfunction, and a higher risk of pulmonary complications such as pneumonia.…”
Section: Discussioncontrasting
confidence: 48%
“…One possible explanation for this finding is that even within etiology groups, older individuals may have lower-energy injuries than younger individuals. Beck and associates 24 found that SCI caused by low falls were more common in persons age 65 years or older, whereas high falls as a cause of SCI were more common in those younger than 65 years old. In addition, high falls were more likely to result in complete paraplegia compared with low falls (24% vs. 5.2%), which are less likely to convert to incomplete than tetraplegia.…”
Section: Discussionmentioning
confidence: 99%